Experimental study of two-phase flow properties of CO2 containing N2 in porous media. Issue 64 (21st June 2016) - Wu, Bohao; Jiang, Lanlan; Liu, Yu; Yang, Mingjun; Wang, Dayong; Lv, Pengfei; Song, Yongchen
Abstract : Saturation comparisons of different total capillary numbers and CO2 fraction in CO2 storage artifact. Abstract : In preliminary analyses, the co-injection of CO2 with H2 S, SO2 and N2 impurities has been shown to reduce total carbon capture and storage (CCS) cost. The multiphase flow properties of impurities in the CO2 –brine system in porous media are the key to understanding the mechanisms and nature of geological CO2 sequestration projects. In this study experiments were performed on the multiphase flow process of CO2 /N2 /brine system at conditions similar to aquifer pressure and temperature using the X-ray CT technique. Experiments at various rates of CO2 injection that affect saturation and spatial distribution of injected gas were conducted in this experiment. The results indicate an strong relationship between gas saturation and porosity distribution in porous media, and the increasing capillary number leads to lower saturation in downward injection. Small capillary numbers and higher fractional flows in the gas phase both result in uniform saturation maps in the core. The CO2 clusters seem larger at high capillary numbers and the high CO2 collection regions extend based on the saturation distribution in the lower CO2 fraction as the flow pattern stays similar as the same capillary number. CO2 containing N2 tends to retain more correlative relationships at different gas injection rates compared with the pure CO2 stream. Even though both distribution and saturation are storage concerns, the N2 component has little effect on gas distribution, whereas it brings about an overall increase in the saturation for most experiments. Thus the N2 enhanced the storage performance of CO2 .